2012
DOI: 10.1104/pp.112.197277
|View full text |Cite
|
Sign up to set email alerts
|

Examination of the Distribution of Arsenic in Hydrated and Fresh Cowpea Roots Using Two- and Three-Dimensional Techniques    

Abstract: Arsenic (As) is considered to be the environmental contaminant of greatest concern due to its potential accumulation in the food chain and in humans. Using novel synchrotron-based x-ray fluorescence techniques (including sequential computed tomography), short-term solution culture studies were used to examine the spatial distribution of As in hydrated and fresh roots of cowpea (Vigna unguiculata 'Red Caloona') seedlings exposed to 4 or 20 mm arsenate [As(V)] or 4 or 20 mm arsenite. For plants exposed to As(V),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
38
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 43 publications
0
38
0
Order By: Relevance
“…Recent advances in synchrotron-based techniques allow in situ measurement of the distribution of metal (loid)s in hydrated fresh plant tissues (Kopittke et al, 2011(Kopittke et al, , 2012Lombi et al, 2011a). In particular, the prototype Maia detector system, jointly developed by the Australian Synchrotron, the Commonwealth Scientific and Industrial Research Organization, and the Brookhaven National Laboratory, represents a newgeneration x-ray fluorescence detector and real-time processing approach that provides unprecedented capabilities in in situ element imaging and measurement (Lombi et al, 2011b).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Recent advances in synchrotron-based techniques allow in situ measurement of the distribution of metal (loid)s in hydrated fresh plant tissues (Kopittke et al, 2011(Kopittke et al, , 2012Lombi et al, 2011a). In particular, the prototype Maia detector system, jointly developed by the Australian Synchrotron, the Commonwealth Scientific and Industrial Research Organization, and the Brookhaven National Laboratory, represents a newgeneration x-ray fluorescence detector and real-time processing approach that provides unprecedented capabilities in in situ element imaging and measurement (Lombi et al, 2011b).…”
mentioning
confidence: 99%
“…roots) without observable damage (Lombi et al, 2011a). This has allowed us to overcome the analytical challenges of examining the two-dimensional and virtual three-dimensional distribution of lowconcentration metal(loid)s in hydrated and fresh plant tissues (Kopittke et al, 2011(Kopittke et al, , 2012Lombi et al, 2011aLombi et al, , 2011c.…”
mentioning
confidence: 99%
“…However, because some of these images [18,19] were generated from whole root mounts and not cross-sections, it was unclear if the elevated As signal in those studies was predominantly on the inside of the roots or on the outside of roots associated with Fe plaques (or both). Other researchers have successfully used computed tomography or modeling approaches to estimate the influx of As in root apices in rice, wheat, and cowpea roots in short-term studies [20,23]. Ma et al [24] demonstrated that lateral roots are important for Si transport in rice, but the importance of these zones for As(III) i root-uptake has only recently been investigated [25].…”
Section: Introductionmentioning
confidence: 99%
“…Using a collimated beam, larger objects, such as works of art, have been imaged at 50-100 µm resolution [18] over areas up to 600 × 300 mm 2 . This method has been applied to studies in the earth [23][24][25][26][27][28][29][30], planetary [31], environmental [32,33], medical [19,34], biological [20][21][22][35][36][37][38][39][40][41] and material [42] sciences as well as cultural heritage [18,43]. A similar capability has been established on the P06 beamline (e.g.…”
Section: Large Area Mappingmentioning
confidence: 99%
“…5 µm tomographic data have been acquired using a KB mirror pair with ~2 µm resolution over ~1 mm specimens [37]. Single-slice data can be obtained from highly radiation-sensitive specimens, such as fresh and fully hydrated plant roots, in a matter of minutes [20,21,38,39]. Measurement of the Ge distribution in an intact rice grain with 2 µm voxels over 2-3 mm dimensions utilized high-definition 2D fluorescence tomography, with 2001 projections and a measurement time of the order of 3 hours [22] (figure 4a).…”
Section: D Fluorescence Tomographymentioning
confidence: 99%